2016
DOI: 10.1039/c6ra02588a
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene and [3]ferrocenophane-based β-diketonato copper(ii) and zinc(ii) complexes: synthesis, crystal structure, electrochemistry and catalytic effect on thermal decomposition of ammonium perchlorate

Abstract: Ferrocene and [3]ferrocenophane-based β-diketonato Cu(ii) complexes exhibit enhanced electrochemical behaviors and burning rate catalytic effects compared with the Zn(ii) complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The experiments revealed that all five sensitizers are redox stable and displayed quasi‐reversible voltammograms. [ 42 ] The HOMO and LUMO energy levels of sensitizers were calculated at the inception of reduction and oxidation potentials. The HOMO levels of these sensitizers are in range from +0.245 to +0.515 V versus Ag/Ag + in acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments revealed that all five sensitizers are redox stable and displayed quasi‐reversible voltammograms. [ 42 ] The HOMO and LUMO energy levels of sensitizers were calculated at the inception of reduction and oxidation potentials. The HOMO levels of these sensitizers are in range from +0.245 to +0.515 V versus Ag/Ag + in acetonitrile.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated feasible charge injection from photoexcited sensitizers in the conduction band of TiO 2. [ 42c ] Also, to ensure fast excited‐state injection and dye regeneration a minimum driving force of 0.2 V is sufficient. Thus, the electron injection from the excited state of the sensitizers to the conduction band of TiO 2 followed by the regeneration of oxidized dyes through a redox couple are highly efficient in all five sensitizers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compounds Ia-8 and Ib-8 with ferrocenyl showed very broad absorption bands at 480-620 nm due to d-d type transitions of the electrons of the iron atoms, and this band for the [3]ferrocenophane-containing Ib-8 was stronger than that of ferrocene-containing 1a-8. 34 Next, the compounds were irradiated with UV light (365 nm). As an example, the spectral changes of Ic are presented in Fig.…”
Section: Photoisomerisation Studiesmentioning
confidence: 99%
“…6, the redox potentials of Ib-8 slightly inuenced by the scan rate in a range from 10 to 300 mV s À1 , and both the anodic and cathodic peak currents are linear to the square root of scan rates, indicating a diffusion-controlled process. 34…”
Section: Electrochemical Investigationmentioning
confidence: 99%